2021
DOI: 10.46966/ijae.v2i2.172
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Implementation of Distance Learning in the COVID-19 Pandemic New Normal Era

Abstract: This research was conducted to see the implementation of distance learning during the New Habitual Adaptation (NHA) period of the COVID 19 pandemic. The indicators that will be seen are planning, implementation, problems, and solutions of distance learning. The method used in this research is a qualitative analysis method. The results of this study are(1) Learning planning for NHA mass education units in Kepahiang Regency has prepared related regulations, and an education unit ordinance has been issued related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(9 reference statements)
0
1
0
3
Order By: Relevance
“…Kendala yang terjadi dalam pembelajaran jarak jauh adalah masih bingungnya guru dalam menentukan model dan media pembelajaran, jaringan internet, fasilitas (laptop atau Handphon), kompetensi guru, dan perbedaan kondisi lingkungan siswa (Alperi et al, 2021). : 2021).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Kendala yang terjadi dalam pembelajaran jarak jauh adalah masih bingungnya guru dalam menentukan model dan media pembelajaran, jaringan internet, fasilitas (laptop atau Handphon), kompetensi guru, dan perbedaan kondisi lingkungan siswa (Alperi et al, 2021). : 2021).…”
Section: Pendahuluanunclassified
“…Dari perjalanan dinamika pembelajaran jarak jauh di masa pandemi telah menyisakan berbagai permasalahan (Alperi, M., Riyanto, R., Sapri, J., Alexon, A., & Handayani, D. : 2021).…”
Section: Hasil Dan Pembahasan 1 Analisis Permasalahanunclassified
See 1 more Smart Citation
“…After all, it is an innovative solution to close the digital divide and make education more accessible. More than 80% of students actively participated in carrying out the adaptation period to new study habits in Kepahiang with the most widely used learning method being the mixed method developed by the teacher himself through the selection of media/methods appropriate learning, cooperation with parents, and careful and effective study planning (Alperi et al, 2021). Finally, the results found that lecturers continued to carry out habituation movements to foster student character values in online learning through habituation by lecturers using backgrounds while studying with character identities that could be inserted values in each lecture (Parmin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%